Remote Triggered Analog Communication Laboratory for e-Learning - Markan, CM; Kumar, Goutam; Mittal, Sajal; Gupta, Priti; Gupta, Satendra; Satsangi, Anshul; Gupta, Ashima; Kapur, Garima (International Journal of Online and Biomedical Engineering (iJOE), 2013)
Currently most universities have Online-learning environments ready to be remotely accessed through the internet. Remote labs have emerged as a viable alternative for developing skills and to learn how to deal with laboratory instruments in the absence of real labs. Remote labs can provide remote access to hardware and simulators, and can allow students to perform experiments without time and location restrictions. In addition, they provide the necessary guidance and also constrain user operation in order to avoid dangerous situations (both from set-up integrity and from the userâ??s point of view). In this paper, we describe a hierarchical model of a remote lab for analog communication that is focused for undergraduate and engineering students. The lab brings together a two level learning approach. i). A basic device level approach for new users and ii). An advanced block level approach for advanced users. Features like on-demand service, virtual breadboard, interactive instrument panels and supporting supplementary materials, makes our lab the right candidate to be used in e-learning. The lab is currently being used for e-learning at distance education centers of the university.